A Reliability Check of Privilege Summaries Printed by Balthasar Moretus I (1610-1641) - Selleslach, Kristof (Early Modern Low Countries, 2024)
Publishers rarely provided the full text of a privilege in their books, instead offering only a summary, often in the language of the publication. Previous research has proved in one instance that the Antwerp printer Balthasar Moretus I (1574-1641) printed a summary which reflected his own desires rather than the terms of the privilege itself: he extended its territorial scope from the Duchy of Brabant to the entire Habsburg Netherlands, and he even cited his mother as a grantee. This incident raises the question how reliable the summaries of printer’s privileges were. For publishers in the Habsburg Netherlands, printed summaries represented the most accessible source of information about their competitors’ privileges. The same applies to present-day scholars. This article investigates the reliability of the privilege summaries printed by Balthasar Moretus I. Through a systematic comparison of the printed summaries with the handwritten original privileges preserved in the Plantin-Moretus archives, the article exposes the patterns of his summarisation method. In providing his summaries, Balthasar Moretus aligned several aspects of the privileges with the Officina Plantiniana’s branding policy. In addition, errors slipped into the summaries that can be attributed to sloppiness in copy-pasting earlier summaries. The result of Balthasar Moretus I’s sleight-of-hand combined with errors in reproduction was that his summaries did not reliably reflect the content of privileges granted to him.